Long-term intermittent fasting improves neurological function by promoting angiogenesis after cerebral ischemia via growth differentiation factor 11 signaling activation - Zhao Liu; Mengjie Liu; Gongwei Jia; Jiani Li; Lingchuan Niu; Huiji Zhang; Yunwen Qi; Houchao Sun; Liang-Jun Yan; Jingxi Ma (PLoS ONE, 2023)
Intermittent fasting (IF), an alternative to caloric restriction, is a form of time restricted eating. IF conditioning has been suggested to have neuroprotective effects and potential long-term brain health benefits. But the mechanism underlying remains unclear. The present study focused on the cerebral angiogenesis effect of IF on ischemic rats. Using a rat middle cerebral artery occlusion model, we assessed neurological outcomes and various vascular parameters such as microvessel density (MVD), regional cerebral blood flow (rCBF), proliferation of endothelial cells (ECs), and functional vessels in the peri-infarct area. IF conditioning ameliorated the modified neurological severity score and adhesive removal test, increased MVD, and activated growth differentiation factor 11 (GDF11)/activin-like kinase 5 (ALK5) pathways in a time-dependent manner. In addition, long-term IF conditioning stimulated proliferation of ECs, promoted rCBF, and upregulated the total vessel surface area as well as the number of microvessel branch points through GDF11/ALK5 pathways. These data suggest that long-term IF conditioning improves neurological outcomes after cerebral ischemia, and that this positive effect is mediated partly by angiogenesis in the peri-infarct area and improvement of functional perfusion microvessels in part by activating the GDF11/ALK5 signaling pathway.